Esplenectomia e outros fatores de risco para hipertensão pulmonar em pacientes com esquistossomose hepatoesplênica - Ferreira, Rita de Cassia dos Santos (2013)
Schistosomiasis is probably the main cause of pulmonary arterial hypertension (PAH) in the world. Splenectomy is used as treatment of upper gastrointestinal bleeding due to rupture of gastroesophageal varices secondary to schistosomal portal hypertension. However, it is a risk factor to PAH in others clinical scenarios, being possible that it increases the risk of PAH in mansonic schistosomiasis. The risk factors that determine the expression of PAH in some individuals with schistosomiasis are unknown. A role of the interleukyn (IL)-13 and transforming growth factor (TGF)-beta is suggested in the pulmonary vascular changes found in animal models of schistosomiasis. This thesis had the main objectives: verify the association of splenectomy and others risk factors with PAH in patients with hepatosplenic schistosomiasis and assess the seric levels of TGF-β and interleukin IL-13 in patients with schistosomal periportal fibrosis with and without PAH. The first article (Splenectomy and others risk factors to pulmonary hypertension associated to mansonic schistosomiasis) describes one case-control study that recruted patients evaluated in outpatient clinic of schistosomiasis in Hospital das Clínicas – Universidade Federal de Pernambuco and outpatient clinic of PAH reference center of Pronto Socorro Cardiológico de Pernambuco. Sixty four patients with hepatosplenic schistosomiaisis splenectomized or not with PAH defined by cardiac catheterization (mean pulmonary arterial pressure ≥25mmHg and pulmonary capillary wedge pressure ≤ 15mmHg) and 173 patients with hepatosplenic schistosomiaisis splenectomized or not, without PAH by transthoracic Doppler echocardiogram (pulmonary arterial systolic pressure ≤ 36mmHg) were enrolled. In the multivariate logistic regression model, splenectomy, thyroid disease increased levels of D dimer were independently associated with an increased risk of PAH. Adrenergic blockers use, previous schistosomal treatment and previous upper gastrointestinal bleeding were associated with a decreased risk of PAH. The second article (TGF-β and interleukin-13 in pulmonary arterial hypertension associated with mansonic schistosomiasis) describes a study conducted with 34 patients without PAH by transthoracic Doppler echocardiogram and 34 patients with PAH by right cardiac catheterization and both groups with schistosomal periportal fibrosis on abdominal ultrasound. They were submitted to assessment of seric dosage of TGF-β and IL-13 by ELISA. A significantly increased median of TGF-β in patients with PAH was found compared to patients without PAH (p=0.006). There was no significant difference regarding the difference between the median of IL-13 in patients with and without PAH (p>0.05). Conclusion: splenectomy and increased levels of D-dimer were independently associated with an increased risk of PAH, suggesting that a pro-thrombotic state occurs in these patients. Thyroid disease was other risk factor. However, previous schistosomal treatment, history of upper gastrointestinal bleeding and use of adrenergic blockers were associated with a decreased risk of PAH. TGF-β may contribute to PAH pathogenesis in schistosomiasis and could be a target of treatment in PAH associated with schistosmisiasis